PENGARUH MEDIA PEMBELAJARAN KARTU KWARTET TERHADAP HASIL BELAJAR SISWA PADA MATERI SEJARAH LAHIRNYA PANCASILA KELAS V DI SD NEGERI SUKOSARI JOGOROTO - Lutfiyah Triwahyuni; Emy Yunita Rahma Pratiwi (JURNAL ILMIAH NUSANTARA, 2025)
There are many problems that occur in the subject of Pancasila and citizenship, especially in the material on the history of the birth of Pancasila, one of which is that learning is still centered on teachers and textbooks only. Students are accustomed to learning with the lecture method. This kind of learning model can create a classroom atmosphere that is not conducive and less active, indicated by the noisy classroom atmosphere, students are busy chatting when the teacher explains in front of the class, therefore causing low student learning outcomes.This study aims to determine the effect of quartet card media on student learning outcomes in the history of the birth of Pancasila for grade V at SD Negeri Sukosari. This study is a quantitative study with a Pre-Experimental Design type of research in the form of One-Group Pre-test-Post-test. The population is all fifth grade students at SD Negeri Sukosari. The sample taken in this study consisted of one class consisting of 20 students. The data collection method used in this study is the test question method. The test is a written test in the form of multiple choices.The results of this study can be concluded that: (1) The learning outcomes of students on the material about the history of the birth of Pancasila in grade V students of Sukosari Elementary School before using the quartet card media are generally categorized as moderate with an average value obtained of 64.40. (2) While after using the quartet card media, it is generally categorized as capable with an average value obtained of 83.60. (3) The influence of the quartet card media on the material on the history of the birth of Pancasila in grade V students of Sukosari Elementary School shows that there is a significant influence of 0.000. The significant value indicating 0.000 <0.05 so that H₀ is rejected and Ha is accepted, which means that there is a significant influence in the use of quartet card media on the learning outcomes of the material on the history of the birth of Pancasila in grade V students of Sukosari Elementary School.